Technical indicators for rational investing in the technology companies: the evidence of FAANG stocks - de Almeida, Luís António Gomes (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper aims to contribute to technical-scientific knowledge about the tools needed to support the decision making in investments in the capital market. We focus our analysis on the following technology companies’ performance: Facebook, Apple, Amazon, Netflix and Google (FAANG). The simulation covers 18,389 observations, applying strategies based on the Ichimoku dynamics, technical analysis indicators, MACD and RSI, and the purchase and maintenance strategy (B&H), that gives evidence that the dynamics of the past is the best predictor for the future. We also found theoretical and empirical evidence of the predictive capacity of these investment strategies, and their performance was evaluated by the return provided, through different negotiation methodologies tested. The Ichimoku system trading dynamics offers the best profitability and the lowest concerning the risk, in the short and medium term, evaluated by the return and number of trades with positive returns.